Cross-Country Heterogeneous Response to Competition: Theory and Evidence from Trade Data - Atrianfar, Hamed; Firooz, Hamid (The Review of Economics and Statistics, 2026)
We document that in response to intensified competition from China in the U.S., poor countries reduce their export prices relative to rich countries, consistent with conventional wisdom. Interestingly, however, the opposite is true for export quantities. To reconcile these facts, we develop and estimate a general equilibrium model of trade featuring (i) cross-country heterogeneity in the ability to produce high-quality goods and (ii) a two-dimensional Bertrand competition on price and quality. Our model explains the empirical facts by showing that rich countries have a comparative advantage in quality upgrading, whereas a nested model without quality cannot do so.